If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(x-2)=5x-12
We move all terms to the left:
7(x-2)-(5x-12)=0
We multiply parentheses
7x-(5x-12)-14=0
We get rid of parentheses
7x-5x+12-14=0
We add all the numbers together, and all the variables
2x-2=0
We move all terms containing x to the left, all other terms to the right
2x=2
x=2/2
x=1
| n/3+6=66 | | 8x-21=x+7 | | 3x+7+(-x)=2x+1+2x+3 | | 25.3/4=-24.3/4+n | | 253/5=-243/4+n | | c+(-1/2)=-1/3 | | c+(-1/2)=-1/2 | | 4z/10+3=-4 | | -52=v/5 | | -s=26 | | x+144=36 | | d-26=7/7/8 | | d-26=7.7/8 | | d-26=77/8 | | 8y+13=29. | | 7x+13=−6x−18 | | x-16.1=-22.8 | | 5x(8-4)=÷4-2 | | -4k+1=47 | | x+x-x=21. | | -4y+4=5y+8 | | 5(2)+(5)+3z=45 | | 5(2)+5+3z=45 | | -4h=-36 | | 52+5+3z=45 | | 2-3c=-5 | | 5x=-2+7 | | 8.1x+2500=65.61+50x | | 3+5*0=x | | r-8=-23 | | 5.4/1.8=7800000/x | | 4(10x−8)2−12(10x−8)+8=0 |